Evaluation of Green Hotel Implementation in Indonesia: Its Impact on Millennial Travelers' Staying Decisions - Ningtyas, Regita Anggia; Falah, Zidnal (Politeknik Siber Cerdika Internasional, 2025)
Sustainability issues are increasingly becoming a major concern in the global hospitality industry. Millennial travelers as the dominant segment in tourism show a strong preference for accommodations that apply environmentally friendly principles or green hotels. This study aims to evaluate the implementation of the green hotel concept in Indonesia and analyze its impact on millennial tourists' stay decisions. The research uses a qualitative approach with a case study method on hotels in Bali, Jakarta, and Bandung. Data collection techniques were conducted through in-depth interviews with hotel management, field observations, and questionnaires to licensed employees. The results showed that green hotel practices are most prominently implemented in the aspects of energy efficiency, the use of local products, and waste management. However, the aspect of sustainability communication to guests is still weak and has not been maximized. The findings also reveal that millennial travelers tend to choose hotels that show a real commitment to sustainability. In conclusion, green hotel implementation has a positive influence on millennial travelers' stay decisions, especially when accompanied by an educative and transparent communication strategy. This research provides important implications for hotel managers and policy makers in promoting sustainable tourism in Indonesia.